(untitled) (International Conference on Education and Innovation, 2025)
This thesis presents the capabilities, practical applications, and main stages of the analysis process within the Simulation (Analysis and Testing) module of Siemens NX software. In modern industry, computer-aided analysis plays a vital role in improving product reliability, creating energy-efficient designs, and reducing manufacturing errors. Using the Simulation module, mechanical stresses, deformations, thermal and dynamic characteristics of structures are modeled based on numerical methods, particularly the Finite Element Method (FEM). The research elaborates the stages of the analysis process — model preparation, adjustment of calculation parameters, solution generation, and result evaluation. Additionally, structural analysis results based on a practical example are provided, and future development directions of the Simulation module, such as multiphysics analyses and AI-based optimization, are discussed.